Social justice for a new Arab era: promoting jobs, protection and dialogue in a changing region : ILO Development Results 2010-2011 - International Labour Organization. Regional Office for the Arab States (Beirut International Labour Organization (ILO), 2012)
Recent regional developments prove that social justice cannot be attained in the absence of basic freedoms. Arab states must move towards an inclusive development model of higher productivity and, together with their citizens, forge a new social contract. Only then can they meet the aspirations of millions of young Arab women and men who will settle for nothing less than a more equitable, just and sustainable future for all
Social justice for a new Arab era ILO in the Arab States -- Creating jobs -- Extending social protection -- Promoting social dialogue -- Guaranteeing rights at work
Keywords: Labour market; LABOUR MARKET; EMPLOYMENT; YOUTH UNEMPLOYMENT; EMPLOYMENT CREATION; RIGHT TO WORK; SOCIAL JUSTICE; ARAB COUNTRIES